Effectiveness of solution focus brief counseling approach (SFBC) in developing student career adaptability - Mulawarman, Mulawarman; Munawaroh, Eem; Nugraheni, Edwindha Prafitra (COUNS-EDU: The International Journal of Counseling and Education, 2016)
Career adaptability is the preparedness role in work and adjustman to changes in working situation in the future. The purpose of this study was to examine Solution Focused Brief Counseling (SFBC) approach in developing career adaptability of students.The method used in this study was a mix method . Subjects selected through a purposive sampling method that is focused on graduate students at the beginning of the semester with a major in Guidance and Counseling Faculty of Education, Semarang State University. Career adaptability in this study consists of four dimensions, concern, control, curiosity and confidence. Stages of Solution Focused Brief Counseling (SFBC) implemented include establishing relationships, Identifying a solvable complaint, Establishing goals, Designing and Implementing Intervention, and termination, evaluation, and follow-up. The results of this study showed Solution Focused Brief Counseling (SFBC) is effective in improving the adaptability of student career both qualitatively and quantitatively.